ANALISIS KINERJA KEUANGAN PT WIJAYA KARYA BETON, Tbk SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) TAHUN 2014 - Zeze Zakaria Hamzah; Suci Sumiati (Institut Teknologi dan Bisnis Dewantara, 2020)
Theoretically the IPO decision gained a big influence in improving the company's condition and improving financial performance. The purpose of this study was to determine the level of financial health. PT Wijaya Karya Beton, Tbk before and after the IPO was measured using a financial ratio and assessed based on the Minister of BUMN Decree No. KEP-100 / MBU /2002. The results of this study are, measured by indicators of ROE ratio, ROI, collection periods and total asset turnover, it can be said that the IPO phenomenon does not have a sufficiently good impact on the financial performance of PT Wijaya Karya Beton, Tbk. While in the period after the IPO it can be said that the phenomenon of the IPO has a good impact on the financial performance of PT Wijaya Karya Beton, Tbk if measured by indicators of the ratio of cash ratios, current ratios, inventory turnover and TMS to TA. Based on BUMIN Ministerial Decree No. KEP-100 / MBU / 2002 on the financial aspects of PT Wijaya Karya Beton, Tbk, the soundness of financial performance in the period before and after the IPO can be said to be healthy with the same assessment of A. But when viewed from the total average weighted assessment, in the period before the IPO the value was better at 55.25 compared to the total average weighted valuation after the IPO period which was 51.16.